IMPROVING ELEMENTARY SCHOOL STUDENTS' ENVIRONMENTAL CARE SKILLS IN UTILIZING PLASTIC BOTTLES AS SOCIAL SCIENCE LEARNING MEDIA - Faridilah Fahmi Nurfurqon; Jajang Bayu Kelana; Deri Fadly Pratama (Universitas Majalengka, 2023)
Garbage is a social problem that until now has become a problem that is difficult to overcome. The problem of waste is very disturbing human activities everyday. Garbage can cause the environment to become dirty, damage the beauty of the surrounding environment, cause bad odors, and become a source of various diseases that can interfere with public health. Therefore, awareness of the environment needs to be cultivated as early as possible, including at the elementary school level. This study aims to improve students' environmental care skills in terms of utilizing plastic bottle waste as social studies learning media in elementary schools. Environmental care skills are part of the character that needs to be developed because love for the environment is a manifestation of love for the motherland, and shows pride as a dignified Indonesian society. This study uses a quasi-experimental method. The population of this study were 5th grade students with a sample of 70 students consisting of 35 control class students and 35 experimental class students. The instruments used are test questions and observation guidelines. The data were processed and analyzed using the SPSS 22 application. The results showed that the comparison between the control class and the experimental class obtained that the average N-Gain value for the experimental class was greater than that of the control class. Thus, the application of learning by utilizing plastic bottles as a learning medium in social studies learning in elementary schools can improve environmental care skills. Sampah merupakan permasalahan sosial yang hingga saat ini menjadi persoalan yang sulit diatasi. Permasalahan sampah sangat mengganggu aktifitas manusia sehari-hari. Sampah dapat menyebabkan lingkungan menjadi kotor, merusak keindahan lingkungan sekitar, menimbulkan bau tidak sedap, hingga menjadi sumber dari berbagai penyakit yang dapat mengganggu kesehatan masyarakat. Oleh karena itu kesadaran akan lingkungan perlu di pupuk sedini mungkin tidak terkecuali di jenjang sekolah dasar. Penelitian ini bertujuan untuk meningkatakan keterampilan peduli lingkungan siswa dalam hal memanfaatkan sampah botol plastik sebagai media pembelajaran IPS di sekolah dasar. Keterampilan peduli lingkungan merupakan bagian dari karakter yang perlu dikembangkan karena kecintaan terhadap lingkungan merupakan perwujudan cinta tanah air, dan menunjukkan kebanggan sebagai masyarakat Indonesia yang bermartabat. Penelitian ini menggunakan metode Quasi Eksperimen. Populasi dari penelitian ini adalah siswa kelas 5 dengan sempel sebanyak 70 siswa yang terdiri dari 35 siswa kelas kontrol dan 35 siswa kelas ekperimen. Adapun instrument yang digunakan adalah soal tes dan pedoman observasi. Data diolah dan dianalisis menggunakan bantuan aplikasi SPSS 22. Hasil penelitian menunjukan bahwa perbandingan antara kelas kontrol dan kelas ekperimen diperoleh nilai rata-rata N-Gain kelas eksperimen lebih besar dari kelas kontrol. Dengan demikian, penerapan pembelajaran dengan memanfaatkan botol plastik sebagai media pembelajaran pada pembelajaran IPS di sekolah dasar dapat meningkatkan keterampilan peduli lingkungan.